A new device for impression transfer for non-parallel endosseus implants - Matteo Danza; Ilaria Zollino; Riccardo Guidi; Francesco Carinci (Elsevier, 2009)
The three-dimensional orientation of dental implant is transferred to a model by means of transfer device and impression material. If more than one implant is inserted and fixtures are not perfectly parallel, the impression may become distorted when removed from the mouth. In this case, a transfer that can be disengaged from the internal implant-abutment connection and removed together with the tray could be useful. An impression transfer device composed of a proper transfer, an inner hexagon and a central screw is described. When the central screw and the hexagon are removed, the proper transfer is free to move horizontally and the tray can be removed from the mouth without distortion of the impression material. Keywords: Implant, Transfer, Parallel, Impression, Analog